Factors Influencing Learning Behavior and Its Implications for Guidance and Counseling Services - Silva Febrina; Asmidir Ilyas (Universitas Negeri Padang, 2020)
Learning behavior is influenced by internal factors and external factors. This research is motivated by the phenomenon of students who have poor learning behavior. This study aims to describe internal and external factors that influence student learning behavior. This type of descriptive research using quantitative methods. The research population of students of SMA Negeri 5 Padang was 1,025 students, and the research sample of 273 students were selected by proportional stratified random sampling technique. Data collection uses a questionnaire about the factors that influence the learning behavior of the Likert Scale model. Data were analyzed using descriptive statistical techniques. The results of this study describe (1) internal factors that influence learning behavior namely physiological aspects are in the high category (50%), and psychological aspects are in the high category (49%), (2) external factors that influence learning behavior namely the social environment in the high category (68%), and the nonsocial environment is in the high category (63%). Based on the research findings, it is suggested to BK teachers to be able to provide Guidance and Counseling services in the form of information services, content mastery services, individual counseling services, group guidance services, and group counseling services to students, so that students can overcome the problems or obstacles they experience.